An early peak in the radio light curve of short-duration gamma-ray burst 200826A. Issue 2 (8th March 2021) - Rhodes, Lauren; Fender, Rob; Williams, David R A; Mooley, Kunal
ABSTRACT: We present the results of radio observations from the eMERLIN telescope combined with X-ray data from Swift for the short-duration gamma-ray burst (GRB) 200826A, located at a redshift of 0.71. The radio light curve shows evidence of a sharp rise, a peak around 4–5 d post-burst, followed by a relatively steep decline. We provide two possible interpretations based on the time at which the light curve reached its peak. (1) If the light curve peaks earlier, the peak is produced by the synchrotron self-absorption frequency moving through the radio band, resulting from the forward shock propagating into a wind medium and (2) if the light curve peaks later, the turnover in the light curve is caused by a jet break. In the former case we find a minimum equipartition energy of ∼3 × 10 47 erg and bulk Lorentz factor of ∼5, while in the latter case we estimate the jet opening angle of ∼9–16°. Due to the lack of data, it is impossible to determine which is the correct interpretation, however due to its relative simplicity and consistency with other multiwavelength observations which hint at the possibility that GRB 200826A is in fact a long GRB, we prefer the scenario one over scenario two.